The Effects of Positive Youth Development Based Classroom Guidance Program on Life Skills of Primary School Students - Günnur Özbay; Serap Nazlı (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study was conducted to determine whether the positive youth development based classroom guidance program affected life skills of primary school students positively. As a quantitative method, a 2x3 split plot pretest –posttest control group semi-experimental design was used. Participants included the fourth-grade students who are attending a public school in Turkey. The experimental group was given the positive youth development based classroom guidance program (12 weeks classroom guidance, 12 weeks workshop training) developed by the researchers. The Life Skills Scale was utilized to determine the life skill levels of the participants. The effects of the guidance program were analyzed by a mixed design ANOVA (2x3). The findings of the research study indicate that the positive youth development-based guidance program had a significant effect on students’ relationships and social interests. The training program implemented has shown that the participants in the experimental group provide an increase in life skills related to the dimension of relationship (managing differences, resolving conflicts, cooperating, social skills and communication), social interest (involving others, empathy, sharing and nurturing relationships). Additionally, a statistically significant difference was observed between the post-test and follow-up test scores of the students in the experimental group. It was found that the effect continued for a month after the training was given to the experimental group.